Oncolytic Bluetongue Viruses: Promise, Progress, and Perspectives - Li, Joseph K. (Frontiers in Microbiology, 2011)
Humans are sero-negative towards Bluetongue viruses (BTVs) since BTVs do not infect normal human cells. Infection and selective degradation of several human cancer cell lines but not normal ones by five US BTV serotypes have been investigated. We determined the susceptibilities of many normal and human cancer cells to BTV-infections and made comparative kinetic analyses of their cytopathic effects (CPEs), survival rates, ultra-structural changes, cellular apoptosis and necrosis, cell cycle arrest, cytokine profiles, viral genome, mRNAs and progeny titers. The wild-type US BTVs, without any genetic modifications, could preferentially infect and degrade several types of human cancer cells but not normal cells. Their selective and preferential BTV-degradation of human cancer cells is viral dose-dependent, leading to effective viral replication and induced apoptosis. Xenograft tumors in mice were substantially reduced by a single intra-tumoral BTV injection in initial in vivo experiments. Thus, wild-type BTVs, without genetic modifications, have oncolytic potentials. They represent an attractive, next generation of oncolytic viral approach for potential human cancer therapy combined with current anti-cancer agents and irradiation.